Akulturasi Islam dan Budaya Lokal dalam Tradisi Tebus Weteng di Desa Mertapada Wetan Cirebon - Muhammad Nizar (Journal of Religion and Social Transformation, 2025)
Tebus Weteng is a cultural tradition of the local community in Desa Mertapada Wetan that continues to be practiced today and has undergone a process of integration with Islamic teachings. This study aims to explore how the integration process between Islam and local culture shapes the Tebus Weteng tradition. The research employs a qualitative method with a case study approach, while data collection techniques include interviews, observation, and documentation. The findings show that Islamic values are integrated into the Tebus Weteng tradition through the recitation of Al-Qur'an verses, the recitation of the Maulid Nabi, communal prayers, and charitable practices in the form of food distribution, all of which reflect the implementation of Islamic teachings. The study's findings suggest that the Tebus Weteng tradition represents a harmonious blending of Islam and local culture, which not only strengthens the religious values of the community but also enhances social solidarity and the preservation of local culture.